Municipal Education Plan of Taubate: monitoring process analyze - Castilho, Eduardo (2022)
This paper aims to analyze the monitoring process and evaluation of the  Municipal Education Plan (2015 - 2025), it discusses had taken actions from public authorities foreseen activities by the Education Municipal Secretary to encourage civil society's participation concerning monitoring and evaluation of PME. This is qualitative research anchored in bibliographic research, document analysis, and a semi-structured interview with technicians from the Education Municipal Secretary, the Education Commission of Municipal Chambar, and the municipal Council for Education.